Preparation and Nutritional Quality Evaluation of Fruit Peel Candies - Nagar, Vaishali; Rastogi, Mayuri (Journal for Research in Applied Sciences and Biotechnology, 2022)
The major motive of this research work is to study the preparation of candies from orange and lemon peels. Citrus peels are the discarded or waste material from citrus fruits which are used as a main ingredient in this research to utilize fruit waste and to reduce harmful effects on the environment and to produce value added products. Orange peels are an excellent source of vit-C, fibre, vit-B6, folic acid, calcium and other nutrients. Due to the presence of naturally occurring chemical limonene they have anti-cancer and anti-inflammatory properties. Lemon peels are a good source of calcium, potassium, fibre, vit-C and healthy enzymes and flavonoids that have antioxidant and anti-cancer properties. Orange and lemon peels were dried to obtain high fibre and vit-C rich powder which is then used to prepare candies. Three samples of candies were prepared- C1(20 g orange peel powder + 100 g sugar), C2 (20 g lemon peel powder + 100 g sugar), C3(10 g orange peel powder+10 g lemon peel powder + 100 g sugar). Physio-chemical properties of candies such as pH, moisture content and Ash content were determined by using AOAC methods. Crude fibre, total sugar, vitamin C content and shelf-life of prepared candy were analysed. Sensory evaluation of candies was done by using hedonic scale.